Plant Terpenoids as Hit Compounds against Trypanosomiasis - Raquel Durão; Cátia Ramalhete; Ana Margarida Madureira; Eduarda Mendes; Noélia Duarte (MDPI AG, 2022)
Human African trypanosomiasis (sleeping sickness) and American trypanosomiasis (Chagas disease) are vector-borne neglected tropical diseases, caused by the protozoan parasites Trypanosoma brucei and Trypanosoma cruzi, respectively. These diseases were circumscribed to South American and African countries in the past. However, human migration, military interventions, and climate changes have had an important effect on their worldwide propagation, particularly Chagas disease. Currently, the treatment of trypanosomiasis is not ideal, becoming a challenge in poor populations with limited resources. Exploring natural products from higher plants remains a valuable approach to find new hits and enlarge the pipeline of new drugs against protozoal human infections. This review covers the recent studies (2016-2021) on plant terpenoids, and their semi-synthetic derivatives, which have shown promising in vitro and in vivo activities against Trypanosoma parasites.